Prevalence of Depression among Lesbian, Gay, Bisexual, Transgender, and Queer in Pokhara, Nepal - Thapa, Shrijana; Maharjan, Pranita; Neupane , Deekshya; Nepal, Susmita (One Health Journal of Nepal, 2021)
Introduction: LGBTQ stands for lesbian, gay, bisexual, transgender, and queer. Depression is a common and serious medical illness that affects your feeling, thinking, and the way you act in a negative way. The main aim of this study was to assess the prevalence of depression in LGBTQ. Methods: A descriptive cross-sectional study was done in Paribartan Nepal, Pokhara. Snowball sampling was used from which 54 samples were taken. The participants were either registered in the organization or referred by it. Self-administered questionnaire was used. Hamilton Depression Rating Scale was used to assess depression. Data were analyzed and interpreted using SPSS version 16.0 through percentages and numbers. Results: Among 54 respondents, the majority were transgender (70.4%) followed by a lesbian (18.5%), gay (5.6%), and bisexual (5.6%). 20.4% had mild depression, 1.9% had moderate depression and 5.6% had severe depression. Transgenders(31.6%) were found to be more depressed than others. Conclusions: About one-third of the LGBTQ respondents were found to be depressed among which transgender(31.6%) were highly depressed comparatively.